Appropriate Removal of Forest Litter is Beneficial to Pinus tabuliformis Carr. Regeneration in a Pine and Oak Mixed Forest in the Qinling Mountains, China - Huo, Xueying; Wang, Dexiang; Bing, Deye; Li, Yuanze; Kang, Haibin; Yang, Hang; Wei, Guoren; Chao, Zhi (Forests, 2019)
Research Highlights: Natural regeneration is important in pine–oak mixed forests (Pinus armandii Franch., Pinus tabuliformis Carr., and Quercus aliena Bl. var. acuteserrata Maxim.ex Wenz.), but allelopathy as a limiting factor has not been studied. Our research provides insights into allelopathy in pine–oak mixed forest litter. Background and Objectives: Allelopathy among tree species occupying the same ecological niche in mixed forests may adversely affect regeneration. We studied allelopathy in pine and oak forest litter to determine the effect on regeneration, whether it is offset by adding activated carbon or plant ash, and what allelopathic substances are present. Materials and Methods: We used laboratory seed culture and field seeding to determine pine and oak litter regeneration effects on P. tabuliformis and P. armandii in the Qinling Mountains, China. In the laboratory, we irrigated seeds with three different litter concentrations. A fourth treatment incorporated activated carbon. The field study established small quadrats in mixed forest to study how removing or retaining litter and spreading plant ash affected sown seeds. High performance liquid chromatography–mass spectrometry was used to compare differences in chemical substances in extracts with and without activated carbon. Results: Litter extracts significantly affected germination rates in both species. Seedling morphological and physiological indexes showed that litter extracts negatively affected growth in both species, but activated carbon alleviated this inhibitory effect on P. armandii. Forest stand and litter did not affect P. armandii seed germination. Pinus tabuliformis germination rates were significantly higher in plots with removed litter than when litter was retained or plant ash spread, and lower in oak than pine forest. Allelopathic substances detected in pine forest were trioctyl trimellitate, amyloid β-Peptide 10–20, and triisobutyl phosphate, potentially affecting P. armandii seed germination and growth. Conclusions: Appropriate removal of litter in mixed forests can improve the natural regeneration ability of P. tabuliformis.